Metropolitan management and agricultural activities: the city dictatorship. Study case, municipality of Málaga, Spain - Gómez-Moreno, María Luisa (My University, 2014)
Montes de Málaga is a slate massif (Betic Mountains). Their successive functions (since XIII century to present) have been determined by the city of Málaga, as an example of the rural-urban relation in Mediterranean area under organic economy. In this paper: 1.-These phases are stated, considering it the origin of the different landscape and settlement units. 2.-Urban planning of Málaga is analysed from the viewpoint of its relationship with agricultural activities. The conclusion that has been got is that several factors hinder the agricultural dynamism of their inhabitants, getting this land in a peripheral rural area that is unable to take the most of their nearness to Costa del Sol, one of the most dynamics metropolitan areas of the European Mediterranean shore. These factors are: 1.-The peasants mentality, linked to small farms structure and yet anchored in the dependence from wine and dry fruits traders. 2.-Urban planning, that is the only planning that bound to landowners and that ignores how agricultural system works. So, this planning focuses in soil or landscape conservation instead of measures that enhance the processes that really generate both values, dependents from agricultural practices. Finally, we expose the means stemmed from the nearness to Málaga city (about 500.000 inhabitants) in order to evolving agricultural activities from the deprivation to the benefits of home market agriculture. In doing so, dependence relationships may be transformed in complementarity one.
Planificación metropolitana y actividades agrarias: la dictadura de la ciudad. Caso de estudio: término municipal de málaga
Keywords: Málaga - Desarrollo económico y social; Protected areas; Urban planning; Local development; Home market agricultura